Membrane-Bound ATPase Contributes to Hop Resistance of Lactobacillus brevis - Sakamoto, Kanta (American Society for Microbiology, 2002)
The activity of the membrane-bound H(+)-ATPase of the beer spoilage bacterium Lactobacillus brevis ABBC45 increased upon adaptation to bacteriostatic hop compounds. The ATPase activity was optimal around pH 5.6 and increased up to fourfold when L. brevis was exposed to 666 μM hop compounds. The extent of activation depended on the concentration of hop compounds and was maximal at the highest concentration tested. The ATPase activity was strongly inhibited by N,N′-dicyclohexylcarbodiimide, a known inhibitor of F(o)F(1)-ATPase. Western blots of membrane proteins of L. brevis with antisera raised against the α- and β-subunits of F(o)F(1)-ATPase from Enterococcus hirae showed that there was increased expression of the ATPase after hop adaptation. The expression levels, as well as the ATPase activity, decreased to the initial nonadapted levels when the hop-adapted cells were cultured further without hop compounds. These observations strongly indicate that proton pumping by the membrane-bound ATPase contributes considerably to the resistance of L. brevis to hop compounds.